A Comparative Study on the Consumption Patterns of Processed Food Among Individuals With and Without Type 2 Diabetes - Anu Mahajan; Aditi Deshmane; Arti Muley (International Journal of Public Health, 2025)
ObjectiveThe study aims to analyse the eating patterns and consumption of ultra-processed food (UPFs) among individuals with and without diabetes.MethodsA comparative cross-sectional study was conducted across Pune, India, with 100 individuals with type 2 diabetes (T2D) and 208 without diabetes. A detailed FFQ (Food Frequency Questionnaire) developed by NOVA-UPF Screener with 33 ultra-processed food items was used to evaluate the consumption patterns of UPF.ResultsMost of the participants with diabetes have a habit of eating breakfast daily (68%), prefer lunch from home (72%), and about 20% avoid eating at a restaurant. While only 45.7% of the participants without diabetes have breakfast daily, and 88.4% prefer to eat lunch outside rather than homemade food. Comparative analysis shows that all 33 UPFs were consumed significantly less by individuals with diabetes than those without diabetes (p < 0.001).ConclusionThe reduced intake of UPFs highlights greater dietary caution among individuals with T2D. Therefore, these findings emphasize the importance of promoting healthy eating habits and limiting UPF consumption among the general population to prevent the onset of metabolic conditions like diabetes.